2012
DOI: 10.1371/journal.pone.0031183
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Bacterial Biofilm Stability by Triclosan

Abstract: The accumulation of the widely-used antibacterial and antifungal compound triclosan (TCS) in freshwaters raises concerns about the impact of this harmful chemical on the biofilms that are the dominant life style of microorganisms in aquatic systems. However, investigations to-date rarely go beyond effects at the cellular, physiological or morphological level. The present paper focuses on bacterial biofilms addressing the possible chemical impairment of their functionality, while also examining their substratum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 70 publications
2
28
1
Order By: Relevance
“…Of prime speculation has been the potential for cascading ecological consequences for stream communities, given demonstrated biofilm-specific effects [22,27,29,31]. Our results equally demonstrated changes in the biofilm community, in terms of bacterial cell density, algal biomass, and algal structure (decreased cyanobacteria densities, potential change in diatom species).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Of prime speculation has been the potential for cascading ecological consequences for stream communities, given demonstrated biofilm-specific effects [22,27,29,31]. Our results equally demonstrated changes in the biofilm community, in terms of bacterial cell density, algal biomass, and algal structure (decreased cyanobacteria densities, potential change in diatom species).…”
Section: Discussionsupporting
confidence: 55%
“…The hypothesis follows that triclosan may be impacting whole ecosystems from ecological cascades, if the basal producers and osmotrophs of streams are sensitive. Several studies have assessed potential effects of triclosan at higher levels of ecological organization, focusing on understanding whether interacting structural and functional changes occur with exposure in river biofilms (also termed periphyton) [22,[26][27][28][29][30][31]. Generally, it can be concluded from these studies that triclosan at relatively low concentrations ( 10 mg/L) could significantly alter periphyton structure and activity.…”
Section: Introductionmentioning
confidence: 99%
“…The DGGE results pointing to a change in community structure are also consistent with both toxic and selective TCS effects. The findings of Drury et al (2013) (8 g g −1 ) and Lubarsky et al (2012) (2-100 g l −1 ) also show that chronic TCS exposure resulted in changes in bacterial community composition and a loss of diversity. Such changes may be due to selective recruitment or inhibition of sensitive species during biofilm development.…”
Section: Response Of the Bacterial Communitymentioning
confidence: 72%
“…In fact, Schreiber and Szewzyk (2008) reported that even nanogram per liter of antimicrobials significantly affected the recruitment of bacteria to the attached community. In contrast, Lubarsky et al (2012) suggested that while surface recruitment was not affected by TCS, biofilm development was inhibited by increasing TCS levels. Morin et al (2010a), utilized in situ incubations to examine effects of pesticides used in vineyards and reported that biofilm dry weight, ash free dry weight, and Chl-a suggested that biofilms translocated to contaminant free sites recovered within two months.…”
Section: Response Of the Bacterial Communitymentioning
confidence: 95%
“…Additionally, they are sensitive to anthropic actions such as eutrophication or antibiotic release in the environment (Lubarsky et al, 2012;Sawall et al, 2012). These biofilms are often very productive and they also provide different ecosystem services, such as nutrient recycling, degradation of pollutants and sediment stabilisation, and they are essential for the recruitment of numerous benthic organisms (Decho, 2000).…”
Section: Introductionmentioning
confidence: 99%